Monitoring and Evaluating the Impact of National School-Based Deworming in Kenya : Study Design and Baseline Results - Mwandawiro, Charles S.; Nikolay, Birgit; Kihara, Jimmy H.; Ozier, Owen; Mukoko, Dunstan A.; Mwanje, Mariam T.; Hakobyan, Anna; Pullan, Rachel L.; Brooker, Simon J.; Njenga, Sammy M. (BioMed Central, 2015)
An increasing number of countries in Africa and elsewhere are developing national plans for the control of neglected tropical diseases. A key component of such plans is school-based deworming (SBD) for the control of soil-transmitted helminths (STHs) and schistosomiasis. Monitoring and evaluation (M&E) of national programs is essential to ensure they are achieving their stated aims and to evaluate when to reduce the frequency of treatment or when to halt it altogether. The article describes the M&E design of the Kenya national SBD program and presents results from the baseline survey conducted in early 2012.